A commensal network of epiphytic orchids and host trees in an Atlantic Forest remnant: A case study revealing the important role of large trees in the network structure. (21st September 2018) - Zotarelli, Henrique G. S.; Molina, José M. P.; Ribeiro, José E. L. S.; Sofia, Silvia H.
Abstract: Application of metrics derived from network theory could elucidate the structural organization of orchid assemblages, and help identify the host tree species on which they depend, as well as predicting the impacts of removing host tree species. In this study, we used nestedness, modularity, connectance and robustness, to identify the factors that predict the structure of a quantitative orchid–host tree network in a remnant of Atlantic Forest in Brazil. The network exhibited low nestedness (NODF = 14.07; P = 0.03; WNODF = 5.3; P = 0.02) and no modularity. It was highly robust to the random elimination of host tree species, but showed low robustness when host trees with more interactions started to be eliminated. The nested pattern found was attributed to a combination of two main host tree traits, height and diameter (given by DBH measure). Thus, our analyses reflect the importance of tall and large host tree species, which seem to play an important role in the network structure, providing a substrate for orchid species with different habitat associations and representing a decisive factor in both nested and robust patterns found.